Latest Trends in Foreign Language Teaching Learning and Curriculum Designing: Exploring the Place and Scope of Arabic Language in Higher Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Arabic language is being taught in the Indian sub-continent for the past several decades and has now found its place in various Universities of India and in other related academic fields. Arabic language has now become an International language, being spoken in several countries both as native as well as a second or foreign language. From the early eighth century, Arabic in India has borne an Islamic identity, which has continued to be elaborated and strengthened through the thirteen centuries of its use under Muslims and British rule. Presently, in India, Arabic language is also being taught and learned in more than twenty thousand Madarsas, mostly in Northern and some Western parts of India. Deobandh and Nadva-tul-Ulum has emerged as the major centers of learning of Arabic language in the form of recitation of Quran and Hadith. These centers of Arabic learning are now also offering post graduate and graduate courses in the teaching of Arabic language. The present paper tries to explore the place and scope of Arabic language in the higher education system of India and the impact of teaching and learning Arabic language on other languages.